2023
DOI: 10.1093/plphys/kiad323
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study unveils ascorbate regulation by PAS/LOV PROTEIN during high light acclimation

Abstract: Varying light conditions elicit metabolic responses as part of acclimation with changes in ascorbate levels being an important component. Here, we adopted a genome-wide association-based approach to characterize the response in ascorbate levels on high light acclimation in a panel of 315 Arabidopsis (Arabidopsis thaliana) accessions. These studies revealed statistically significant SNPs for total and reduced ascorbate under high light conditions at a locus in chromosome 2. Ascorbate levels under high light and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…In Arabidopsis plants, the CONSTITUTIVE PHOTOMORPHOGENIC9-Signalosome subunit 5B (CSN5B) has been reported to negatively regulate ascorbate biosynthesis by being involved in the degradation of GMP proteins during the dark period (Wang et al, 2013). Recently, Aarabi et al (2023) reported the PAS/LOV protein (PLP) as a novel ascorbate regulator, which suppresses ascorbate biosynthesis by interacting with GGP in the dark, and light irradiation resolves this association and allows GGP to function, thereby increasing ascorbate levels. In M. polymorpha, both CSN5B and PLP orthologs are present in the genome (Mapoly0006s0112.1 and Mapoly0022s0166.1, respectively), and their involvement in ascorbate biosynthesis will need to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis plants, the CONSTITUTIVE PHOTOMORPHOGENIC9-Signalosome subunit 5B (CSN5B) has been reported to negatively regulate ascorbate biosynthesis by being involved in the degradation of GMP proteins during the dark period (Wang et al, 2013). Recently, Aarabi et al (2023) reported the PAS/LOV protein (PLP) as a novel ascorbate regulator, which suppresses ascorbate biosynthesis by interacting with GGP in the dark, and light irradiation resolves this association and allows GGP to function, thereby increasing ascorbate levels. In M. polymorpha, both CSN5B and PLP orthologs are present in the genome (Mapoly0006s0112.1 and Mapoly0022s0166.1, respectively), and their involvement in ascorbate biosynthesis will need to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%